Synthesis of an adaptive cylindrical gear with arched teeth with two contact zones spaced along the length of the tooth - V. N. Syzrantsev; A. I. Starikov (Омский научный вестник, 2023)
Cylindrical gears with arched teeth have the required performance in conditions of both non-rigid machine bodies and inevitable manufacturing and assembly errors. Error compensation is carried out by self-alignment of the wheels, the possibilities of which are limited in gears with one line of engagement. The article investigates an adaptive gear with arched teeth with two contact zones, which provides selfalignment of the wheels, regardless of the angle of misalignment of the teeth in engagement. The most promising in terms of implementation in the industry method of cutting arched teeth with a circular cutter head by the rolling method with a single division on CNC machines. Solved and illustrated by examples of the problem of calculating the parameters of the process of shaping the surfaces of arched teeth, which ensure the passage of two active lines in the meshing of the teeth through the given centers of the contact patches and the law of change of the transfer function required for the implementation of the approximate nature of the meshing.